2022
DOI: 10.1039/d2em00102k
|View full text |Cite
|
Sign up to set email alerts
|

Emerging investigator series: contributions of reactive nitrogen species to transformations of organic compounds in water: a critical review

Abstract: Reactive nitrogen species (RNS) pose a potential risk to drinking water quality because they react with organic compounds to form toxic byproducts. Since the discovery of RNS formation in sunlit...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 154 publications
0
11
0
Order By: Relevance
“…Previous studies indicated that nitrogen would incorporate into some organic substances to form toxic nitrogenous disinfection byproducts (e.g., nitroaromatic compounds, among which nitrophenols are of particular concern due to high toxicity) during UV 254 disinfection of nitrate-containing water. ,, To investigate whether nitrogenous byproducts are formed during UV 222 photolysis of nitrate, phenol was used as a byproduct precursor, with consideration that (1) phenol is highly reactive toward RNS and (2) dissolved organic matter in water is usually rich in phenolic moieties. , The formation of nitrophenols during UV 222 photolysis of nitrate in deionized water containing phenol increased with increasing the initial nitrate concentrations and UV fluence (Figures S10 and b). The conversion rate of nitrophenols (total molar concentrations of nitrophenols formed per molar concentration of phenol consumed) also increased from 24.74–26.98% to 30.84–33.81% with the increase of initial nitrate concentration from 0.5 to 10 mg-N L –1 (Figure b) ( p = 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated that nitrogen would incorporate into some organic substances to form toxic nitrogenous disinfection byproducts (e.g., nitroaromatic compounds, among which nitrophenols are of particular concern due to high toxicity) during UV 254 disinfection of nitrate-containing water. ,, To investigate whether nitrogenous byproducts are formed during UV 222 photolysis of nitrate, phenol was used as a byproduct precursor, with consideration that (1) phenol is highly reactive toward RNS and (2) dissolved organic matter in water is usually rich in phenolic moieties. , The formation of nitrophenols during UV 222 photolysis of nitrate in deionized water containing phenol increased with increasing the initial nitrate concentrations and UV fluence (Figures S10 and b). The conversion rate of nitrophenols (total molar concentrations of nitrophenols formed per molar concentration of phenol consumed) also increased from 24.74–26.98% to 30.84–33.81% with the increase of initial nitrate concentration from 0.5 to 10 mg-N L –1 (Figure b) ( p = 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to radicals formed in situ from background water constituents. With the background absorbance being 15-fold higher at 222 nm than at 254 nm, it is likely that appreciable concentrations of radicals were formed from organic matter, nitrate, and/or carbonate in the water, including singlet oxygen, •OH, and reactive nitrogen species, which may all have contributed to CBZ degradation. , For NDMA, the degradation rate constant under LPUV, LPUV/H 2 O 2 , KrCl* excimer lamp, and KrCl*/H 2 O 2 systems decreased by 50%, 20%, 30%, and 30% in SE, respectively, compared to LGW. The decrease in the NDMA degradation rate constant in SE compared to LGW for all UV systems is most likely due to light screening because the background absorbance increased by 15-fold, and AOPs play minimal role in NDMA degradation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…With the background absorbance being 15-fold higher at 222 nm than at 254 nm, it is likely that appreciable concentrations of radicals were formed from organic matter, nitrate, and/or carbonate in the water, including singlet oxygen, •OH, and reactive nitrogen species, which may all have contributed to CBZ degradation. 41,42 For NDMA, the degradation rate constant under LPUV, LPUV/H 2 O 2 , KrCl* excimer lamp, and KrCl*/H 2 O 2 systems decreased by 50%, 20%, 30%, and 30% in SE, respectively, compared to LGW. Similar to the results in LGW, the H 2 O 2 concentration decreased at a significantly higher rate under the filtered KrCl* excimer lamp than under LPUV, as shown in Tables S1 and S2 for H 2 O 2 concentrations in CBZ and NDMA experiments, respectively.…”
Section: Uv and Uv/aop Inmentioning
confidence: 99%
“…nitrogen dioxide ˙NO 2 ) and other intermediates. [1][2][3][4] These oxidants may react with organic compounds in water, contributing to their degradation and lifetime in the environment. 3 In addition, the combination of UV light and NO 3 − can be regarded as an advanced oxidation process (AOP), degrading organic contaminants during water and wastewater treatments.…”
Section: Introductionmentioning
confidence: 99%